IMPROVEMENT OF CORPORATE GOVERNANCE AS A RESULT OF CAPITAL MARKET DEVELOPMENT AND IMPROVEMENT OF THE LEGAL AND REGULATORY ENVIRONMENT IN THE REPUBLIC OF SERBIA - Petrović, Jelena; Orlandić, Milja; Marković, Sanja Anastasija (Journal of process management and new technologies, 2023)
The framework of corporate governance in the Republic of Serbia is determined by relevant laws and by-laws. Today’s regulations are on the trail of targeted European standards, and a bigger problem is manifested in their application than in the quality of individual legal solutions. With the primary goals of enhancing transparency and defending the interests of minority shareholders, pertinent legal measures have recently implemented additional requirements for public corporations as well as majority owners. The issue at hand is how much public company managers believe the legal and regulatory environment has improved corporate governance. On the other hand, the domestic capital market continued to flourish without receiving the crucial attention of the political and economic authorities. The Belgrade Stock Exchange, the sole operator of the regulated market and multilateral trading platform, is required to list all publicly traded firms in the Republic of Serbia’s shares for trading on the exchange. The stock market in the Republic of Serbia still doesn’t serve as a location for getting additional (equity or debt) capital, or only seldom does so, despite the undeniable advancements in the organisation and trading system. However, the arrival of new (institutional) investors on the Belgrade Stock Exchange brought changes and set new standards not only among direct market participants but also among managers and majority owners of public companies. For years, the reporting rules of public companies have been one of the regular obligations of their managers. It is important to know how much public company managers believe the growth of the stock market has contributed to better corporate governance.